Beyond the Piazza Public and Private Spaces in Modern Italian Culture - Storchi, Simona (Moving texts / Testi mobili, 2013)
The volume is a collection of essays focussing on the cultural construction, perception and representation of public and private spaces in 20th and 21st century Italian culture. Through the study of a variety of spaces, this book provides an exploration of the notions of private self and public sphere and considers their interaction. It focuses on areas where the spheres of public and private merge, meet or clash, and assesses the role played by spatial practices and representations in the complex coexistence, mutual definition and constant negotiation of public and private. It offers a variety of approaches, ranging from literature to history, art history, film and cultural studies. It brings to the fore issues relating to the production of space, such as perceptions and definitions of the self and privacy, the politics of the private and public, gender representations, the construction of collective and cultural memory, and the relationship between the individual and the urban environmnent